Chastʹ zapadnago berega poluostrova Kamchatki ot paralleli 58°15' N do paralleli 58°45' N po opisi Gidrograficheskoĭ Ėkspedit︠s︡īi Vostochnago okeana 1914 g. / Chertili Shturmanʺ d. pl. Ivanovskiĭ i Kap. mal. pl. Gragĭtisʺ - Russia. Glavnoe gidrograficheskoe upravlenīe (Vladivostok : Morskoe ministerstvo, Glavnoe gidrograficheskoe upravlenīe; Владивосток : Морское министерство, Главное гидрографическое управленіе, 1914)
Relief shown by form lines and spot heights. Depth shown by soundings.; Title translation: Part of northern coast of the Kamchatka Peninsula, according to the Hydrographic Expedition of the Eastern Sea 1914.; "No. 396" -- top right margin Grayscale; 1:750,464